Infrastructure and Income Inequality in Indonesia: 2009-2017 - Wiastuti Nurdina (Pusbindiklatren Bappenas, 2021)
In the economic development field, physical and social infrastructure have been argued to affect income inequality despite the mixed results. This study examines the impact of physical and social infrastructure (education and health) on income inequality in Indonesia using 34 provincial unbalanced panel data during 2009-2017. Infrastructure summary indices are constructed, and the impacts of infrastructure on income inequality are estimated by the Generalized Method of Moments (GMM). The findings conclude that physical and social (education) infrastructure contributes to income inequality increases in Indonesia though not robustly significant. Regarding health infrastructure, this study cannot definitely infer its nexus with income inequality since only the model of one-step different-GMM is significant. The result implies that the government needs to consider providing better distribution of infrastructure among income groups to improve income distribution.